Answer:
P(n) = 0.5
Step-by-step explanation:
For two events which are independent, we use the multiplication rule which states P (A and B) = P(A) * P(B). Substitute P(m) = 0.4 and P(m and n) = 0.2 into this formula.
P (m and n) = P(m) * P(n)
0.2 = 0.4*P(n)
Divide by 0.4 on both sides.
0.2 / 0.4 = P(n)
0.5 = P(n)
Answer:
113
Step-by-step explanation:
Answer:
d
Step-by-step explanation:
Hope this helps! Good luck!
Simply substitute the value of
3
given. In other words,
f
(
3
)
is the function of
f
(
x
)
, however, in this case,
x
is
3
f
(
3
)
=
3
(
3
)
−
4
Distribute
3
through the parenthesis
f
(
3
)
=
9
−
4
Simplify
f
(
3
)
=
5
Recheck the answer with your teacher.